Lightweight neutron shielding material and method of manufacturing the same
By developing a method for preparing lightweight neutron shielding materials, the shortcomings of neutron shielding materials in terms of high-temperature stability and density have been overcome, enabling the manufacture of low-density, high-strength neutron shielding materials suitable for the design requirements of new reactors.
Patent Information
- Application Number
- CN202511658873.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-13
- Publication Date
- 2026-01-27
- Estimated Expiration
- 2045-11-13
AI Technical Summary
Existing neutron shielding materials are insufficient to meet the design requirements of new reactors in terms of high-temperature stability and density. Conventional hydrogen polymers have insufficient heat resistance, heavy concrete has too high density, and metal hydride materials are brittle and difficult to manufacture into bulk materials.
Lightweight neutron shielding materials are prepared using yttrium powder, gadolinium powder, and boron powder as raw materials through pre-hydrogenation treatment, mixing, cold pressing, and hydrogenation sintering. The high-temperature stability of yttrium hydride and the neutron absorption performance of gadolinium are utilized, combined with the low density characteristics of boron, to form a microstructure in which yttrium gadolinium hydride, gadolinium oxide, and dispersed boron particles are dispersed in a yttrium hydride matrix.
A low-density, high-strength neutron shielding material bulk was prepared, exhibiting good thermal stability and low cracking risk, making it suitable for the service environment of new reactors.
Smart Images

Figure CN121105179B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nuclear power, specifically relating to a lightweight neutron shielding material and its manufacturing method. Background Technology
[0002] With the rapid development of nuclear power technology, higher requirements are being placed on the comprehensive performance of neutron shielding materials. Due to the inherent trend towards increased safety and miniaturization in some new reactor designs, neutron shielding materials need to possess better high-temperature stability and lower density while maintaining neutron absorption capacity. Existing conventional hydrogen polymers and heavy concrete suffer from insufficient high-temperature stability and excessive density, making them unsuitable for the design requirements of new reactors. Therefore, providing a method for manufacturing lightweight neutron shielding materials has significant practical value. Summary of the Invention
[0003] The purpose of this invention is to provide a method for manufacturing a lightweight neutron shielding material, thereby optimizing the overall performance of the neutron shielding material. This invention also provides a lightweight neutron shielding material.
[0004] According to one embodiment of the present invention, a method for manufacturing a lightweight neutron shielding material is provided, the method comprising the following steps:
[0005] Step a): Yttrium powder, gadolinium powder and boron powder are provided as raw materials, and the yttrium powder and gadolinium powder are pre-hydrogenated in a flowing hydrogen atmosphere at 200℃-900℃ for 1h-24h to obtain hydrogenated yttrium powder and hydrogenated gadolinium powder.
[0006] Step b): The yttrium hydride powder, gadolinium hydride powder and boron powder are mixed to obtain a mixed powder, wherein the mixed powder contains 0.5%-20% Gd and 0.1%-10% B by mass ratio.
[0007] Step c): The mixed powder is cold-pressed at 100MPa-300MPa to obtain a cold-pressed blank;
[0008] Step d): The cold-pressed billet is subjected to hydrogenation sintering in a flowing hydrogen atmosphere at 1000℃-1400℃ for 1h-24h to obtain a lightweight neutron shielding material. The matrix of the lightweight neutron shielding material is yttrium hydride, and yttrium gadolinium hydride particles, gadolinium oxide particles and dispersed boron particles are dispersed in the yttrium hydride matrix.
[0009] This method can provide low-density neutron shielding material bulk and reduce the risk of neutron shielding material cracking during sintering.
[0010] Furthermore, in some embodiments, in step a), the average particle size of yttrium powder and gadolinium powder is 200-400 mesh, and the average particle size of boron powder is 100-500 mesh.
[0011] Furthermore, in some embodiments, in step a), the hydrogen flow rate is 0.1 L / min to 1 L / min.
[0012] Furthermore, in some embodiments, in step b), a mixer is used for mixing, with a mixing speed of 3000 r / min-20000 r / min and a mixing time of 5 min-30 min.
[0013] Furthermore, in some embodiments, in step c), the holding time for the cold pressing process is 1 min to 30 min.
[0014] Furthermore, in some embodiments, in step d), the hydrogen flow rate is 0.1 L / min to 2 L / min.
[0015] According to another aspect of the present invention, a lightweight neutron shielding material is provided, which is manufactured using the manufacturing method of the lightweight neutron shielding material provided in any of the foregoing embodiments.
[0016] Furthermore, in some embodiments, the lightweight neutron shielding material has a hardness of not less than 230 HV and a density of not more than 4.4 g / cm³. 3 .
[0017] Furthermore, in some embodiments, the coefficient of thermal expansion of the lightweight neutron shielding material is 8.02-15.8 × 10⁻⁶. -6 / K.
[0018] Furthermore, in some embodiments, the weight of a single block of the lightweight neutron shielding material is not less than 50g. Attached Figure Description
[0019] Figure 1 Photograph of a lightweight neutron shielding material in one embodiment;
[0020] Figure 2 An X-ray image of a lightweight neutron shielding material in one embodiment;
[0021] Figure 3 This is a scanning electron microscope image of the microstructure of a lightweight neutron shielding material in one embodiment.
[0022] The purpose of the above figures is to provide a detailed description of the invention so that those skilled in the art can understand the technical concept of the invention, and not to limit the invention. Detailed Implementation
[0023] The present invention will now be described in further detail with reference to specific embodiments and accompanying drawings.
[0024] The term "embodiment" as used herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment herein. The phrase appearing in various places in the specification does not necessarily refer to the same embodiment, nor is it limited to mutually exclusive, independent, or alternative embodiments. Those skilled in the art will understand that the embodiments herein can be combined with other embodiments without causing structural conflicts.
[0025] In this article, "multiple" means at least two.
[0026] With the development of nuclear power technology, neutron shielding materials face increasingly demanding service environments and stringent performance requirements in miniaturized and micro-sized reactor designs. In some new reactor designs, neutron shielding materials operate at temperatures ranging from 600℃ to 1000℃. Furthermore, due to the need for mobile deployment in some reactor designs, the density of neutron shielding materials must be minimized to optimize system weight. Currently, conventional hydrogen-containing polymers lack sufficient heat resistance, while light water, heavy water, and heavy concrete have excessively high densities, all of which fail to fully meet the design requirements of new reactors. Some metal hydride materials are considered promising candidates for neutron shielding; however, metal hydrides generally exhibit significant brittleness and are typically present in powder form, making it difficult to manufacture them into bulk materials of a certain volume.
[0027] To overcome the shortcomings of the prior art, one embodiment of the present invention provides a method for manufacturing a lightweight neutron shielding material, the method comprising the following steps:
[0028] Step a): Provide yttrium powder, gadolinium powder, and boron powder as raw materials. Among them, yttrium hydride has good fast neutron moderation ability and high-temperature thermal stability, gadolinium has a thermal neutron absorption cross section as high as 49,000 gahn, and boron (… 10 B) It has good neutron absorption properties, and its density is only 2.34 g / cm³. 3 This facilitates the lightweighting of neutron shielding materials. Yttrium powder and gadolinium powder are loaded into a hydrogenation furnace and pre-hydrogenated in a flowing atmosphere at 200℃-900℃ for 1-24 hours to obtain yttrium-hydrogenated powder and gadolinium-hydrogenated powder. Specifically, in a preferred embodiment, the average particle size of the yttrium and gadolinium powders is 200-400 mesh, and the average particle size of the boron powder is 100-500 mesh; the hydrogen flow rate during the pre-hydrogenation treatment is 0.1 L / min-1 L / min.
[0029] Step b): Yttrium hydride powder, gadolinium hydride powder, and boron powder are loaded into a mixer and mixed to obtain a mixed powder. In a preferred embodiment, the mixer speed is set to 3000 r / min-20000 r / min, and the mixing time is set to 5 min-30 min. The composition of the mixed powder is controlled so that, by mass ratio, Gd accounts for 0.5%-20% and B accounts for 0.1%-10%. Mechanical mixing ensures uniform mixing of the raw material powders, thereby improving the uniformity of the final product's structure.
[0030] Step c): The mixed powder is loaded into a mold and cold-pressed at 100MPa-300MPa to obtain a cold-pressed blank. The holding time for cold pressing is controlled between 1min and 30min.
[0031] Step d): The cold-pressed billet is loaded into a hydrogenation furnace, and flowing hydrogen gas is introduced. Hydrogenation sintering is carried out in a flowing hydrogen atmosphere at 1000℃-1400℃ for 1h-24h to obtain a lightweight neutron shielding material. Specifically, in a preferred embodiment, the hydrogen flow rate during hydrogenation sintering is 0.1L / min-2L / min. During sintering, the pores in the cold-pressed billet become diffusion channels for hydrogen gas. While reducing the hydrogen concentration gradient from the surface to the interior, these pores provide buffer space for the raw material powder to further absorb hydrogen and undergo volume expansion due to phase transformation, thereby further reducing the internal stress of the bulk material and lowering the risk of cracking.
[0032] The lightweight neutron shielding material prepared by the above method has a hardness of no less than 230 HV and a density of no more than 4.4 g / cm³. 3 It possesses good strength and low density. Its coefficient of thermal expansion ranges from 8.02 to 15.8 × 10⁻⁶ at temperatures up to 900℃. -6 Due to the excellent thermal stability of yttrium hydride, this neutron shielding material does not undergo significant thermal decomposition below 1000℃. The above method enables the preparation of 100g-sized bulk neutron shielding material, demonstrating significant engineering application value.
[0033] In the first preferred embodiment, the manufacturing process of the lightweight neutron shielding material is as follows:
[0034] First, gadolinium powder and yttrium powder with an average particle size of 200 mesh and boron powder with an average particle size of 325 mesh were selected as raw materials. The gadolinium powder and yttrium powder were loaded into a hydrogenation furnace, vacuumed, and then filled with hydrogen to atmospheric pressure. The vacuuming was repeated twice to remove residual impurities in the furnace. Subsequently, hydrogen was introduced into the hydrogenation furnace at a flow rate of 0.4 L / min, and the furnace was heated to 500℃ and held for 8 hours for pre-hydrogenation treatment to obtain hydrogenated yttrium powder and hydrogenated gadolinium powder.
[0035] Next, yttrium hydride powder, gadolinium hydride powder, and boron powder were loaded into a mixer and mechanically mixed to obtain a mixed powder. The mass ratio of Gd to B in the mixed powder was controlled to be 7% and 0.1%. The mixer speed was set to 15000 r / min and the mixing time to 10 min.
[0036] Next, the mixed powder is loaded into a mold, and the mold is placed into a cold isostatic press and cold-pressed at 220MPa for 3 minutes to obtain a cold-pressed blank.
[0037] Finally, the cold-pressed billet is placed into a high-temperature, high-pressure hydrogenation furnace, and two vacuum cleaning operations are performed to remove impurities from the furnace. Then, hydrogen gas is introduced at a flow rate of 0.6 L / min, and the furnace is heated to 1350℃ and held for 4 hours for hydrogenation sintering, yielding the desired product. Figure 1 The image shows a 100g lightweight neutron shielding material block. X-ray inspection of this lightweight neutron shielding material was performed, as shown... Figure 2 As shown, the material is internally uniform and dense, without pores or cracks. The microstructure of this lightweight neutron shielding material is as follows: Figure 3 As shown, the matrix region 1 is yttrium hydride, in which yttrium gadolinium hydride particles 2 are scattered. Since Gd, as a rare earth element, has a strong tendency to bind with oxygen, a small amount of gadolinium oxide particles 3 are also distributed in the tissue, while fine boron particles are diffused in the tissue.
[0038] The average hardness of this lightweight neutron shielding material was measured to be 234.3 HV, and its density was 4.39 g / cm³. 3 The coefficient of thermal expansion at temperatures ranging from 100℃ to 900℃ is 8.02-15.8×10⁻⁶. -6 / K, the weight loss due to dehydrogenation below 1000℃ is about 0.1%.
[0039] In the second preferred embodiment, the manufacturing process of the lightweight neutron shielding material is as follows:
[0040] First, gadolinium powder and yttrium powder with an average particle size of 400 mesh and boron powder with an average particle size of 500 mesh were selected as raw materials. The gadolinium powder and yttrium powder were loaded into a hydrogenation furnace, vacuumed, and then filled with hydrogen to atmospheric pressure. The vacuuming was repeated twice to remove residual impurity gases in the furnace. Subsequently, hydrogen was introduced into the hydrogenation furnace at a flow rate of 0.1 L / min, and the furnace was heated to 900℃ and held for 1 hour for pre-hydrogenation treatment to obtain hydrogenated yttrium powder and hydrogenated gadolinium powder.
[0041] Next, yttrium hydride powder, gadolinium hydride powder, and boron powder are loaded into a mixer for mechanical mixing to obtain a mixed powder. The mass ratio of Gd to B in the mixed powder is controlled to be 20% and 0.1%. The mixer speed is set to 20,000 r / min, and the mixing time is 5 min.
[0042] Next, the mixed powder is loaded into a mold, and the mold is placed into a cold isostatic press and cold-pressed at 300MPa for 1 minute to obtain a cold-pressed blank.
[0043] Finally, the cold-pressed billet is loaded into a high-temperature and high-pressure hydrogenation furnace, and two vacuum cleaning operations are performed to remove impurities from the furnace. Then, hydrogen is introduced at a flow rate of 2L / min, and the furnace is heated to 1000℃ and held for 24 hours for hydrogenation sintering to obtain a 100g lightweight neutron shielding material block.
[0044] In the third preferred embodiment, the manufacturing process of the lightweight neutron shielding material is as follows:
[0045] First, gadolinium powder and yttrium powder with an average particle size of 325 mesh and boron powder with an average particle size of 100 mesh were selected as raw materials. The gadolinium powder and yttrium powder were loaded into a hydrogenation furnace, vacuumed, and then filled with hydrogen to atmospheric pressure. The vacuuming was repeated twice to remove residual impurity gases in the furnace. Subsequently, hydrogen was introduced into the hydrogenation furnace at a flow rate of 1 L / min, and the furnace was heated to 200°C and held for 24 hours for pre-hydrogenation treatment to obtain hydrogenated yttrium powder and hydrogenated gadolinium powder.
[0046] Next, yttrium hydride powder, gadolinium hydride powder, and boron powder are loaded into a mixer for mechanical mixing to obtain a mixed powder. The mass ratio of Gd to B in the mixed powder is controlled to be 0.5% and 10%, respectively. The mixer speed is set to 3000 r / min, and the mixing time is 30 min.
[0047] Next, the mixed powder is loaded into a mold, and the mold is placed into a cold isostatic press and cold-pressed at 100MPa for 30 minutes to obtain a cold-pressed blank.
[0048] Finally, the cold-pressed billet is loaded into a high-temperature and high-pressure hydrogenation furnace, and two vacuum cleaning operations are performed to remove impurities from the furnace. Then, hydrogen is introduced at a flow rate of 0.1 L / min, and the furnace is heated to 1400℃ and held for 1 hour for hydrogenation sintering to obtain a 100g lightweight neutron shielding material block.
[0049] In the fourth preferred embodiment, the manufacturing process of the lightweight neutron shielding material is as follows:
[0050] First, gadolinium powder and yttrium powder with an average particle size of 200 mesh, as well as boron powder with an average particle size of 200 mesh, were selected as raw materials. The gadolinium powder and yttrium powder were loaded into a hydrogenation furnace, evacuated, and then filled with hydrogen to atmospheric pressure. The furnace was then evacuated again, and this process was repeated twice to remove any residual impurities in the furnace. Subsequently, hydrogen was introduced into the hydrogenation furnace at a flow rate of 0.3 L / min, and the furnace was heated to 700°C and held for 5 hours for pre-hydrogenation treatment to obtain hydrogenated yttrium powder and hydrogenated gadolinium powder.
[0051] Next, yttrium hydride powder, gadolinium hydride powder, and boron powder are loaded into a mixer for mechanical mixing to obtain a mixed powder. The mass ratio of Gd to B in the mixed powder is controlled to be 15% and 5% respectively. The mixer speed is set to 10,000 r / min and the mixing time is 15 min.
[0052] Next, the mixed powder is loaded into a mold, and the mold is placed into a cold isostatic press and cold-pressed at 150MPa for 20 minutes to obtain a cold-pressed blank.
[0053] Finally, the cold-pressed billet is loaded into a high-temperature and high-pressure hydrogenation furnace, and two vacuum cleaning operations are performed to remove impurities from the furnace. Then, hydrogen is introduced at a flow rate of 1L / min, and the furnace is heated to 1200℃ and held for 12 hours for hydrogenation sintering to obtain a 100g lightweight neutron shielding material block.
[0054] In the fifth preferred embodiment, the manufacturing process of the lightweight neutron shielding material is as follows:
[0055] First, gadolinium powder and yttrium powder with an average particle size of 400 mesh, as well as boron powder with an average particle size of 400 mesh, were selected as raw materials. The gadolinium powder and yttrium powder were loaded into a hydrogenation furnace, evacuated, and then filled with hydrogen to atmospheric pressure. The furnace was then evacuated again, and this process was repeated twice to remove any residual impurities in the furnace. Subsequently, hydrogen was introduced into the hydrogenation furnace at a flow rate of 0.7 L / min, and the furnace was heated to 400°C and held for 14 hours for pre-hydrogenation treatment to obtain hydrogenated yttrium powder and hydrogenated gadolinium powder.
[0056] Next, yttrium hydride powder, gadolinium hydride powder, and boron powder were loaded into a mixer and mechanically mixed to obtain a mixed powder. The mass ratio of Gd to B in the mixed powder was controlled to be 5% and 8% respectively. The mixer speed was set to 7000 r / min and the mixing time to 20 min.
[0057] Next, the mixed powder is loaded into a mold, and the mold is placed into a cold isostatic press and cold-pressed at 250MPa for 10 minutes to obtain a cold-pressed blank.
[0058] Finally, the cold-pressed billet is loaded into a high-temperature and high-pressure hydrogenation furnace, and two vacuum cleaning operations are performed to remove impurities from the furnace. Then, hydrogen is introduced at a flow rate of 1.5L / min, and the furnace is heated to 1100℃ and held for 16 hours for hydrogenation sintering to obtain a 100g lightweight neutron shielding material block.
[0059] The purpose of the above embodiments is to provide a detailed description of the present invention so that those skilled in the art can understand the technical concept of the invention, and not to limit the invention. Within the scope of the present invention, optimizations or equivalent substitutions of the technical features involved, as well as combinations of implementation methods in different embodiments without causing structural or principle conflicts, all fall within the protection scope of the present invention.
Claims
1. A method for manufacturing a lightweight neutron shielding material, characterized in that, Includes the following steps: Step a): Yttrium powder, gadolinium powder and boron powder are provided as raw materials, and the yttrium powder and gadolinium powder are pre-hydrogenated in a flowing hydrogen atmosphere at 200℃-900℃ for 1h-24h to obtain hydrogenated yttrium powder and hydrogenated gadolinium powder. Step b): The yttrium hydride powder, gadolinium hydride powder and boron powder are mixed to obtain a mixed powder, wherein the mixed powder contains 0.5%-20% Gd and 0.1%-10% B by mass ratio. Step c): The mixed powder is cold-pressed at 100MPa-300MPa to obtain a cold-pressed blank; Step d): The cold-pressed billet is subjected to hydrogenation sintering in a flowing hydrogen atmosphere at 1000℃-1400℃ for 1h-24h to obtain a lightweight neutron shielding material. The matrix of the lightweight neutron shielding material is yttrium hydride, and yttrium gadolinium hydride particles, gadolinium oxide particles and dispersed boron particles are dispersed in the yttrium hydride matrix.
2. The method for manufacturing the lightweight neutron shielding material according to claim 1, characterized in that, In step a), the average particle size of yttrium powder and gadolinium powder is 200-400 mesh, and the average particle size of boron powder is 100-500 mesh.
3. The method for manufacturing the lightweight neutron shielding material according to claim 1 or 2, characterized in that, In step a), the hydrogen flow rate is 0.1 L / min to 1 L / min.
4. The method for manufacturing the lightweight neutron shielding material according to claim 1 or 2, characterized in that, In step b), a mixer is used for mixing, with a mixing speed of 3000 r / min-20000 r / min and a mixing time of 5 min-30 min.
5. The method for manufacturing the lightweight neutron shielding material according to claim 1 or 2, characterized in that, In step c), the holding time for the cold pressing process is 1 min to 30 min.
6. The method for manufacturing the lightweight neutron shielding material according to claim 1 or 2, characterized in that, In step d), the hydrogen flow rate is 0.1 L / min to 2 L / min.
7. A lightweight neutron shielding material, characterized in that, It is manufactured using the manufacturing method of the lightweight neutron shielding material as described in any one of claims 1 to 6.
8. The lightweight neutron shielding material according to claim 7, characterized in that, The lightweight neutron shielding material has a hardness of not less than 230 HV and a density of not more than 4.4 g / cm³. 3 .
9. The lightweight neutron shielding material according to claim 7, characterized in that, The coefficient of thermal expansion of the lightweight neutron shielding material is 8.02-15.8×10⁻⁶. -6 / K.
10. The lightweight neutron shielding material according to claim 7, characterized in that, The weight of a single block of the lightweight neutron shielding material is not less than 50g.
Citation Information
Patent Citations
Preparation method of crack-free zirconium hydride neutron moderation material
CN113501716A
Preparation method of flexible neutron composite shielding body based on metal hydride
CN115926216A